Analisis Kepuasan Mahasiswa Dalam Menggunakan Aplikasi Digitalent Terhadap Program Pelatihan Bersertifikasi Dengan Metode End User Computing Satisfaction (EUCS) dan Importance Performance Analysist (IPA) - Cyndika; Saluza, Imelda; Yulianti, Evi (Jurnal Ilmiah Informatika Global, 2025)
This study aims to evaluate student satisfaction with the use of the Digitalent application using the End-User Computing Satisfaction (EUCS) and Importance-Performance Analysis (IPA) methods, with analysis conducted through the Statistical Package for the Social Sciences (SPSS) software. The study involved 100 respondents who had used the Digitalent application. The analysis revealed an expectation score of 4.33 and a perceived performance score of 4.26, resulting in an average satisfaction gap (GAP) of –0.08. The variable with the highest gap was accuracy (–0.16), while the smallest gap was found in timeliness (–0.01). The IPA quadrant mapping highlighted several indicators that require improvement, as well as those that should be maintained. Overall, the Digitalent application is considered effective and beneficial for users, although some aspects still need enhancement to reduce the satisfaction gap and improve the overall user experience. This study concludes that Digitalent effectively supports the achievement of digital training goals, particularly for students.